Protein synthesis game: Utilizing game-based approach for improving communicative skills in A-Levels biology class / Mohd Adlan Ramly … [et al.] - Ramly, Mohd Adlan; Kamal Ikhsan, Nurul Aida; Abdul Rahman, Nur Rahimatul Hayati; Ramlan, Norlizayati (Penerbit UiTM (UiTM Press), 2017)
This experimental paper seeks to elucidate the usage of the card game ‘Protein Synthesis Game’ as a student’s learning tool in studying the Biology topic of protein synthesis during an A-Level course. A total of 24 experimental students in 3 induced groups and 24 controlled students in controlled groups were involved in the experiment which began with a pretest on the topic of Protein Synthesis, followed by the experimentation, and ended with a post-test administered after the incubation period. Results indicate that students have better facilitative communicative engagement in learning protein synthesis when playing the game as compared to studying the topic from a book. The data suggests that such communicative engagement may lead to a successful meaningful learning on the students’ part.